Risk factors of foodborne parasitic diseases still remain in China: a WeChat-based knowledge, attitudes, and practices study - Bixian Ni; Qiang Zhang; Feng Tang; Jiayao Zhang; Fanzhen Mao; Yaobao Liu (BMC, 2024)
Abstract Objective With the progress of economic globalization and food diversification, foodborne parasitic diseases pose a significant public health challenge in China. This study aimed to explore the knowledge, attitudes, and practices regarding foodborne parasitic diseases among the Chinese population via WeChat, which is a promising tool for disease surveillance and health education. Methods Using a questionnaire, this cross-sectional study was conducted on September 25, 2023. Participants completed a structured questionnaire by scanning a QR code provided in a tweet from the WeChat official account of the Jiangsu Institute of Parasite Disease. Multivariable logistic regression analysis was employed to explore potential independent determinants of adequate knowledge of foodborne parasitic diseases, and the positive attitude and good practice rates of the participants were calculated. Results In total, 5,675 valid questionnaires were collected via the WeChat official account. Most participants (79.91%) fell within the age range of 20-40 years, with a higher representation of males (53.18%), and 89.80% were of Han Chinese ethnicity. It was found that 76.65% of the participants had adequate level of knowledge. Multivariable logistic regression analysis revealed that individuals of Hui nationality (OR = 0.57, 95% CI: 0.40-0.81, p = 0.002), clinicians (OR = 0.13, 95% CI: 0.09-0.19, p < 0.001), teachers (OR = 0.48, 95% CI: 0.34-0.69, p < 0.001), and government staff (OR = 0.40, 95% CI: 0.30-0.53, p < 0.001) had significantly higher levels of knowledge. Among the participants, 33.9% reported consuming raw fish or drunken shrimp, 10.6% would still try to consume raw fish despite the risk of parasitic infection, and 84.1% did not use separate cutting boards for raw and cooked foods in their kitchens. Conclusions Although majority of the Chinese public (76.65%) demonstrates adequate level of knowledge on foodborne parasitic diseases, there is a need to enhance personal hygiene practices and dietary habits, particularly the utilization of distinct cutting boards and the consumption of raw fish. A WeChat official account is an accessible tool for spreading foodborne parasitic diseases related health information to the public. WeChat-based health education should be implemented to enhance public awareness regarding the prevention and control of foodborne parasitic diseases.